INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN KOMUNIKASI BAHASA ARAB: IMPLIKASI PSIKOLINGUISTIK DAN SOSIOLINGUISTIK - Rohmatul Ummah, Vina (At-Turost : Journal of Islamic Studies, 2024)
In the current digital era, the integration of technology into Arabic language learning has become increasingly important. This study aims to explore the impact of digital technology on the learning process and communication skills in Arabic, as well as the emerging psycholinguistic and sociolinguistic implications. The research employs a mixed methods approach, involving data collection through surveys, interviews, and observations among students learning Arabic. Descriptive statistical analysis is used to evaluate the influence of digital technology on communication skills, while qualitative analysis is employed to understand the dynamics of social interaction in the learning context. The findings indicate that the use of digital technology significantly enhances students' speaking and writing skills in Arabic. Furthermore, digital technology also affects patterns of social interaction, with students being more inclined to communicate through digital platforms compared to face-to-face interactions. The sociolinguistic implications of these findings reveal changes in study group dynamics and social structures within the classroom. This study highlights the importance of understanding both the positive and negative impacts of digital technology on Arabic language learning. With a deeper understanding of the psycholinguistic and sociolinguistic implications, educators can develop more effective approaches to integrating digital technology into the Arabic language curriculum. This research is expected to make a significant contribution to the development of Arabic language education in the digital age.